Aetiological overlap between obsessive–compulsive related and anxiety disorder symptoms: Multivariate twin study. (January 2016) - López-Solà, Clara; Fontenelle, Leonardo F.; Bui, Minh; Hopper, John L.; Pantelis, Christos; Yücel, Murat; Menchón, José M.; Alonso, Pino; Harrison, Ben J.
Abstract : Background: The aetiological boundary between obsessive–compulsive related disorders (OCRDs) including obsessive–compulsive disorder (OCD) and anxiety disorders is unclear and continues to generate debate. Aims: To determine the genetic overlap and the pattern of causal relationships among OCRDs and anxiety disorders. Method: Multivariate twin modelling methods and a new regression analysis to infer causation were used, involving 2495 male and female twins. Results: The amount of common genetic liability observed for OCD symptoms was higher when considering anxiety disorders and OCRDs in the model v. modelling OCRD symptoms alone. OCD symptoms emerged as risk factors for the presence of generalised anxiety, panic and hoarding symptoms, whereas social phobia appeared as a risk factor for OCD symptoms. Conclusions: OCD represents a complex phenotype that includes important shared features with anxiety disorders and OCRDs. The novel patterns of risk identified between OCD and anxiety disorder may help to explain their frequent co-occurrence.